1997
DOI: 10.1088/0022-3727/30/22/001
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial films of exhibiting CMR prepared using nebulized spray pyrolysis

Abstract: Nebulized spray pyrolysis has been employed to deposit thin films of cation-deficient on substrates. The epitaxial nature of these films has been established by x-ray diffraction as well as high-resolution electron microscopy of the interface. The films show magnetoresistance around 210 K at 6 T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
(16 reference statements)
1
6
0
Order By: Relevance
“…This behaviour is similar to that observed in the single-crystal La-manganites [10,17]. Large MRs over a wide range of temperature and at relatively small external magnetic fields have been observed in randomly oriented polycrystalline materials [18][19][20][21]. Wang et al [10] have shown that polycrystalline bulk LCMO exhibits MRs over a wide temperature range and they have attributed this to the presence of weak-link type grain boundaries.…”
Section: Introductionsupporting
confidence: 74%
“…This behaviour is similar to that observed in the single-crystal La-manganites [10,17]. Large MRs over a wide range of temperature and at relatively small external magnetic fields have been observed in randomly oriented polycrystalline materials [18][19][20][21]. Wang et al [10] have shown that polycrystalline bulk LCMO exhibits MRs over a wide temperature range and they have attributed this to the presence of weak-link type grain boundaries.…”
Section: Introductionsupporting
confidence: 74%
“…Several other studies [240][241][242][243][244][245][246][247][248][249] using polycrystalline films have probed the role of grain boundaries in samples consisting of multiple grains with different orientations over the measurement distance of the probe contacts, which gives only qualitative information because the total MR contribution is a complex convolution of the MR due to 'intrinsic' CMR contribution inside the grain and 'extrinsic' contribution coming from the GBs. Bicrystal substrates consisting of a single-grain boundary, with a well-defined misorientation between the grains, are ideal for the growth of films in order to isolate the contribution of a single-grain boundary.…”
Section: Magnetotransport In a Crystal Having Bicrystal Grain Boundarymentioning
confidence: 99%
“…Different techniques have been used to prepare polycrystalline films of La 1-x Ca x MnO 3 on different type of substrates. These include laser ablation [46,[232][233][234]248,250], chemical vapour deposition [246] and spray pyrolysis [249]. Of these techniques the last one, viz., spray pyrolysis is convenient and capable of producing films similar to those produced by more sophisticated techniques like laser ablation [46,[232][233][234]248,250].…”
Section: Studies On Polycrystalline La 067 Ca 033 Mno 3 (Lcmo) Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…From application point of view thin polycrystalline films having significant magneto-resistance at low magnetic field are important. The technique of spray pyrolysis has emerged as quite effective technique to grow good quality polycrystalline thin films having smaller particle size and infinite layer manganite thin films have been successfully deposited and have been found to exhibit significant magneto-resistance both at low as well as high magnetic fields [12][13][14]. In this paper we report the preparation, structural/micro-structural and magneto-transport characterization of La 1.4 Ca 1.6 Mn 2 O 7 polycrystalline films prepared by nebulized spray pyrolysis on single crystal LaAlO 3 substrates.…”
Section: Introductionmentioning
confidence: 99%